A case of crescentic glomerulonephritis in a patient with COVID-19 infection: A case report and literature review. Issue 7 (18th February 2022) - Alawad, Mouhammad J.; Subahi, Eihab A.; Al-Ani, Haneen A.; Taha, Noheir M.; Kamal, Ijaz
Abstract: Rationale: Kidney involvement with COVID-19 infection is a well-known complication, and the majority of kidney involvement is related to ischemic injury/acute tubular injury. However, there are some cases of glomerulonephritis, the etiology of which is not yet known, but an immune process is likely to be the trigger. Patient concerns: A 27-year-old man presented to our hospital with facial puffiness and lower-limb swelling. Diagnosis: Laboratory assessment revealed features of impaired kidney function with proteinuria and hematuria; COVID-19 polymerase chain reaction was positive, which was consistent with pauci-immune crescentic focal segmental glomerulonephritis. Intervention: After renal biopsy, the patient was started on methylprednisolone and rituximab. Due to worsening kidney parameters, he underwent intermittent hemodialysis as needed. Outcome: Kidney function tests partially improved; he was discharged on oral steroids with follow-up in the nephrology clinic to observe for the need for further hemodialysis. Lessons: We conducted a literature review of cases of glomerulonephritis associated with COVID-19 and described numerous types of glomerulonephritis. This report highlights the importance of recognizing emerging glomerulonephritis with COVID-19, the different pathological patterns of renal biopsies, and management interventions and responses.